2009
DOI: 10.1016/s0924-9338(09)71086-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of MMSE to Identify Mild Cognitive Impairment (MCI). A Population-Based Study

Abstract: Aims:To evaluate the prevalence of MCI and its subtypes in the Faenza Project, using the Mini-Mental State Examination (MMSE).Methods:Subjects living in the municipality of Faenza were clinically assessed. The diagnosis of MCI was achieved according to international criteria using a double-step procedure: first, we excluded subjects with dementia, functional impairment and MMSE< 24, leaving 6,745 persons. Then, the performance in different cognitive domains was considered and scores less than 1.5 standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The best cutoff point detecting cognitive disorders in illiterate patients was 18 of 19; and among those educated, the best cutoff point was 24 of 25, 13 Although MMSE offers modest accuracy for ruling out a diagnosis of MCI, 14 it has widely been used in both clinical practice and research and suggested as a useful instrument in screening for cognitive impairment in the guidelines for the Report of the Quality Standards Subcommittee of the American Academy of Neurology. 15…”
Section: Methodsmentioning
confidence: 99%
“…The best cutoff point detecting cognitive disorders in illiterate patients was 18 of 19; and among those educated, the best cutoff point was 24 of 25, 13 Although MMSE offers modest accuracy for ruling out a diagnosis of MCI, 14 it has widely been used in both clinical practice and research and suggested as a useful instrument in screening for cognitive impairment in the guidelines for the Report of the Quality Standards Subcommittee of the American Academy of Neurology. 15…”
Section: Methodsmentioning
confidence: 99%